Choice of surgical tactic at patients with brain magistral arteries stenosis and occlusion - N. A. Zorin; S. P. Grygoruk; I. E. Plyushchev; Raed R. A. Sobh; Yu. V. Cherednichenko; A. Yu. Miroshnichenko (Ukrainian Neurosurgical Journal, 2006)
An experience of 1246 patients treatment with brain magistral arteries stenosis and occlusion is presents. To 496 of them surgical treatment was performed with the use of open surgical and endovascular methods of revascularization. The necessary investigation volume and treatment tactic choice criteria were defined.